Block copolymer self-assembly directed hierarchically structured materials from nonequilibrium transient laser heating - Tan, Kwan Wee (2020)
We highlight two recent approaches operating far from equilibrium for the synthesis of hierarchical porous thin film materials by coupling block copolymer-directed self-assembly with transient laser heating. In first block copolymer-induced writing by transient heating experiments, or B-WRITE, an all-organic block copolymer-resols hybrid film is heated by submillisecond carbon dioxide laser irradiation, directly generating 3D mesoporous continuous resin structures and shapes. Harnessing the highly unique resin materials properties under laser heating conditions, in the second approach block copolymer-directed resin templating is coupled with nanosecond pulsed excimer laser annealing to generate complementary crystalline silicon nanostructures. The underlying structure formation mechanisms for such laser-induced organic and inorganic nanostructured materials are discussed, emphasizing that the nonequilibrium nature of these transient laser annealing approaches opens up vast and new processing windows beyond traditional stability limits of organic polymer materials. Finally, we highlight opportunities and challenges for possible future research directions and applications of laser-induced block copolymer-directed hierarchical porous materials formation including structure control, materials diversification, scale-up, on-chip applications, and additive manufacturing, which may provide solutions in areas as diverse as catalysis, sensing, and energy storage and conversion.